Multiple telescoping flow diverter technique in endovascular treatment of a vertebrobasilar dissecting aneurysm: case report - Wang, Ming-Yi; Liu, Yong-Sheng; An, Xiang-Bo; Pan, Tao; Wang, Feng (Frontiers in Neurology, 2023)
A 64-year-old man presented with headache and dizziness. A vertebrobasilar dissecting aneurysm was identified via computed tomography angiography and high resolution magnetic resonance imaging. Perioperatively, standard oral dual antiplatelet drugs were given. Two flow diverters were telespcoped for endovascular treatment of the aneurysm. Postoperatively, there were no signs of cerebral infarction and no new symptoms. At the 6-month follow-up, digital subtraction angiography showed that the aneurysm was almost completely occluded, with no other complications. This case serves as a reference for using the multiple telescoping flow diverter technique to treat vertebrobasilar dissecting aneurysm.